Calling 911 in response to stroke: no change following a four-year educational campaign - Mikulík, Robert; Goldemund, David; Reif, Michal; Brichta, Jaroslav; Neumann, Jiří; Jarkovský, Jiří; Krýza, J (Cerebrovascular diseases, 2011)
BACKGROUND: Public awareness campaigns are conducted to increase stroke awareness, yet evidence of their long-term effectiveness is limited. Since 2006, the Czech Stroke Society has conducted an educational campaign throughout the Czech Republic (CR) to increase awareness about stroke. This report evaluates the effectiveness of this campaign by comparing the results of a nationwide survey on stroke awareness in 2009 with the results from 2005. METHODS: In 2009, a nationwide survey was conducted throughout the CR using the same methodology as in 2005 and employing a 3-stage random sampling method (area, household, and household member sampling). Participants >40 years of age were personally interviewed via a structured questionnaire concerning their knowledge and ability to correctly respond to stroke as assessed by the validated Stroke Action Test (STAT). The primary outcome measure was the difference in a STAT score >50% (i.e. respondents chose to call 911 for >50% of stroke symptoms) between 2005 and 2009. Campaign intensity was characterized by a systematic search for media messages about stroke in the CR. RESULTS: A total of 601 interviews were obtained (90% response rate) in 2009 (592 people were interviewed in 2005). A STAT score >50% was achieved by 18% of the respondents both in 2005 and 2009 (p = 0.89). There was no increase in the knowledge of risk factors or warning signs between 2005 and 2009. Respondents who noticed the campaign (19%) had better STAT scores than respondents who did not (25 vs. 17%; p = 0.038). A systematic search revealed that the campaign had reasonable intensity because there were 978 media reports about stroke between 2006 and 2008. CONCLUSIONS: A medium-intensity educational campaign, based on donated advertising media, failed to increase stroke awareness. However, if the campaign had reached more people, it might have been effective. Therefore, in the future, paid advertising media should accompany free media, although such approach would require a substantially larger budget. Awareness campaigns should be constantly evaluated for their effectiveness to develop more successful strategies.
Keywords: Health Education; sběr dat; Humans; Longitudinal Studies; lidé středního věku; Risk Factors; dítě; hodnocení výsledků zdravotní péče; Stroke; Child; Emergency Medical Service Communication Systems; Female; rizikové faktory; mladý dospělý; dospělí; Aged; zdraví - znalosti, postoje, praxe; senioři; lidé; Data Collection; předškolní dítě; cévní mozková příhoda; Adult; Follow-Up Studies; komunikační systémy urgentních lékařských služeb; ženské pohlaví; longitudinální studie; Male; Middle Aged; Retrospective Studies; Adolescent; Czech Republic; Aged, 80 and over; zdravotní výchova; Young Adult; senioři nad 80 let; retrospektivní studie; Health Knowledge, Attitudes, Practice; Česká republika; mužské pohlaví; Child, Preschool; Outcome Assessment, Health Care; následné studie; mladiství; uvědomování si; Awareness